Hands-On Deep Learning for Images with TensorFlow : Build Intelligent Computer Vision Applications Using TensorFlow and Keras. - Ballard, Will (Packt Publishing Ltd, 2018)
Chapter 4: A Convolutional Neural Network; Convolutions; Pooling; Building a convolutional neural network; Deep neural network; Summary; Chapter 5: An Image Classification Server; REST API definition; Trained models in Docker containers; Making predictions; Summary; Other Books You May Enjoy; Index.